Canopy disturbance and gap partitioning promote the persistence of a pioneer tree population in a near‐climax temperate forest of the Qinling Mountains, China. Issue 13 (6th June 2019) - Guo, Yaoxin; Zhao, Peng; Yue, Ming
Abstract: An unresolved question of temperate forests is how pioneer tree species persist in mature forests. In order to understand the responsible mechanisms, we investigated a near‐climax mixed temperate forest dominated by Betula albosinensis in the Qinling Mountains of China. Through establishing four 50 m × 50 m plots, we examined the canopy disturbance characteristics and its effects on tree recruitments. We further test the intra‐ and interspecific effects on the recruitment of B. albosinensis . The obtained data demonstrated canopy disturbance was frequent but most small‐sized. The canopy gaps are caused mainly by adult B. albosinensis by snapping. The regeneration of coexistent tree species shows a distinct preference for gap size. B. albosinensis were clumped at the juvenile stage and small scales. B. albosinensis juveniles were positively associated with B. utilis juveniles and negatively associated with the conspecific and B. utilis large trees. In addition, B. albosinensis juveniles showed negative associations with contemporary other tree species. Our results suggested that canopy disturbance caused by canopy trees and gap partitioning among the coexistent tree species are important for the persistence of the mixed forest. As a main gapmaker, B. albosinensis appear to develop a self‐perpetuating life‐history trait and allow them to persist. Abstract : This study aims to provide an insight into the mechanism responsible for the persistence of pioneer Betula albosinensis in mature temperate forests by analysis of canopy disturbance, regeneration mode, and spatial pattern. The results demonstrate that canopy disturbance caused by canopy trees and gap partitioning among the coexistent tree species are important for the persistence of B. albosinensis in the mature mixed forest. B. albosinensis appear to develop a self‐perpetuating life‐history trait and allow them to persist.